Manejo integrado de los principales insectos plaga del cultivo de guanábana (Annona muricata L.) - Noboa Bustamante, Luis Enrique (2021)
The present work corresponded to the practical component of the degree examination of a complex nature, carried out through bibliographic research on different websites, based on the subject of study "Integrated management of the main pest insects of the soursop crop (Annona muricata L.)". The conclusions determine that among the insect pests that have been identified in the soursop crop are Cratosomus sp. (stem cutter); Corythucha gossypii (Lace bug); Bephratelloides maculicollis (Soursop wasp); Thecla ortygnus (Soursop moth); Cerconota anonella (Seed borer) and Toxoptera aurantii (Aphids), taking into consideration so that they do not become potential pests in the medium and long term; The management of microclimatic conditions such as temperature, luminosity, humidity and execution of controlled pruning is a viable strategy to reduce the incidence of pests of the soursop crop and biological control is the best pest control, using yellow polyethylene covers to Cover the fruits, which is an activity that can reduce the weight of the fruit, but it is effective for controlling insects by avoiding chemical products